2020
DOI: 10.1177/2010105820957370
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tacrolimus versus cyclosporine on one-year renal transplant outcomes: A single-centre retrospective cohort study

Abstract: Background: Calcineurin inhibitors are the cornerstone of maintenance immunosuppression after kidney transplant. While studies on predominantly Caucasian populations recommend tacrolimus over cyclosporine, the effects on Singapore’s local population remain unclear. Objectives: This study aimed to compare the impact of tacrolimus against cyclosporine on post-transplant outcomes in our local kidney transplant population. Methods: A single-centre retrospective chart review was conducted on ABO- and human leucocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The association between chronic exposure to tacrolimus or MMF and post‐transplant hCMV infection has been extensively investigated. Both drugs may increase the risk of hCMV tissue‐invasive disease compared to cyclosporine or azathioprine, respectively 92–95 . As no direct comparison can be made between patients with or without hCMV‐GID who receive different immunosuppressive schemes, the value of our findings in confirming this theory is limited.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The association between chronic exposure to tacrolimus or MMF and post‐transplant hCMV infection has been extensively investigated. Both drugs may increase the risk of hCMV tissue‐invasive disease compared to cyclosporine or azathioprine, respectively 92–95 . As no direct comparison can be made between patients with or without hCMV‐GID who receive different immunosuppressive schemes, the value of our findings in confirming this theory is limited.…”
Section: Discussionmentioning
confidence: 81%
“…Both drugs may increase the risk of hCMV tissue-invasive disease compared to cyclosporine or azathioprine, respectively. [92][93][94][95] As no direct comparison can be made between patients with or without hCMV-GID who receive different immunosuppressive schemes, the value of our findings in confirming this theory is limited. mTORi may reduce the incidence and severity of various post-transplant viral infections, including hCMV.…”
Section: Histological Findingsmentioning
confidence: 77%
“…This clearly indicates that an ID protocol based on tacrolimus seems to be more harmful in aspect of VD, in comparison to a regimen based on CsA. According to Ong et al [37], tacrolimus is considered to be almost 100 times stronger than CsA. On the other hand, both the immature fetal liver and placenta can metabolise drugs.…”
Section: Discussionmentioning
confidence: 95%
“…Mycophenolate mofetil belongs to D group, described as confirmed risk for human fetus. According to the literature, comparing the two used CNIs, TAC is more toxic than CsA [37]. Regarding the comparison between MMF and EVE, they exhibit a similar strength of action [38].…”
Section: Discussionmentioning
confidence: 99%
“…Ong et al [ 11 ] conducted a single-center retrospective study comparing the impact of tacrolimus against cyclosporine on post-transplant outcomes in the kidney transplant population. In this study, they found comparable short-term post-transplant outcomes between cyclosporine and tacrolimus.…”
Section: Discussionmentioning
confidence: 99%